Rhabdomyolysis and exercise-associated hyponatremia in ultra-bikers and ultra-runners - Chlíbková, Daniela (J Int Soc Sports Nutr, 2015)
BACKGROUND: Exercise-associated hyponatremia (EAH), rhabdomyolysis and renal failure appear to be a unique problem in ultra-endurance racers. METHODS: We investigated the combined occurrence of EAH and rhabdomyolysis in seven different ultra-endurance races and disciplines (i.e. multi-stage mountain biking, 24-h mountain biking, 24-h ultra-running and 100-km ultra-running). RESULTS: Two (15.4 %) ultra-runners (man and woman) from hyponatremic ultra-athletes (n = 13) and four (4 %) ultra-runners (four men) from the normonatremic group (n = 100) showed rhabdomyolysis following elevated blood creatine kinase (CK) levels > 10,000 U/L without the development of renal failure and the necessity of a medical treatment. Post-race creatine kinase, plasma and urine creatinine significantly increased, while plasma [Na(+)] and creatine clearance decreased in hyponatremic and normonatremic athletes, respectively. The percentage increase of CK was higher in the hyponatremic compared to the normonatremic group (P < 0.05). Post-race CK levels were higher in ultra-runners compared to mountain bikers (P < 0.01), in faster normonatremic (P < 0.05) and older and more experienced hyponatremic ultra-athletes (P < 0.05). In all finishers, pre-race plasma [K(+)] was related to post-race CK (P < 0.05). CONCLUSIONS: Hyponatremic ultra-athletes tended to develop exercise-induced rhabdomyolysis more frequently than normonatremic ultra-athletes. Ultra-runners tended to develop rhabdomyolysis more frequently than mountain bikers. We found no association between post-race plasma [Na(+)] and CK concentration in both hypo- and normonatremic ultra-athletes.